From effectiveness to sustainability: understanding the impact of CARE's Community Score Card© social accountability approach in Ntcheu, Malawi. (12th November 2021) - Mgoli Mwale, Patience; Msiska, Thumbiko; Chinkhota, Kriss; Munthali, Tapiwa; Wako, Etobssie; Rodriguez, Mariela; Laterra, Anne; Shato, Thembekile; Sebert Kuhlmann, Anne
Abstract: We evaluated the sustainability of CARE's Community Score Card© (CSC) social accountability approach in Ntcheu, Malawi, approximately 2.5 years after the end of formal intervention activities. Using a cross-sectional, exploratory design, we conducted 41 focus groups with members of Community Health Advisory Groups (CHAGs) and youth groups and 19 semi-structured interviews with local and district government officials, project staff, and national stakeholders to understand how and in what form CSC activities are continuing. Focus groups and interviews were audio-recorded, transcribed and translated into English. Thematic coding was done using Dedoose software. Most groups were continuing to meet and implement the CSC, although some made modifications. CHAGs, youth and local government officials all attributed their continued implementation to the value that they saw in the process that allows marginalized groups within the community, including women and youth, a safe space for sharing their ideas and issues and the initial results this generated. However, lack of access to resources for implementation and challenges in convening and facilitating the interface meeting phase created barriers to continued sustainability. The CSC is sustainable by communities 2.5 years after the end of formal intervention activities. For future interventions, health systems and non-governmental organizations should plan for a transition phase with periodic refresher trainings and a small fund to support implementation, such as refreshments and transportation, to increase the likelihood of community-driven sustainability.